2016
DOI: 10.1039/c5dt03504j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the flexibility in MOFs by SBU functionalization

Abstract: A new approach for the fine tuning of flexibility in MOFs, involving functionalization of the secondary building unit, is presented. The "gate pressure" MOF [Zn3(bpydc)2(HCOO)2] was used as a model material and SBU functionalization was performed by using monocarboxylic acids such as acetic, benzoic or cinnamic acids instead of formic acid in the synthesis. The resulting materials are isomorphous to [Zn3(bpydc)2(HCOO)2] in the "as made" form, but show different structural dynamics during the guest removal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…[12][13][14][15] Furthermore,n one of these studies explore the concept demonstrated herein, which tackles the development of an ovel crystalline metal-donor-acceptor framework, in which control of the mutual orientation of the donor and fullerenebased acceptor was achieved through chemical bond formation, that is,m etal coordination. Despite the tremendous interest in self-assemblies (in particular,c oordination polymers such as covalent or metal-organic frameworks;COFs or MOFs) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and fullerene chemistry,t ot he best of our knowledge the prepared metal-organic fullerene-containing framework is the first example of ac rystalline hybridextended structure,inw hich control over mutual orientation of both donor and fullerene-based acceptor is achieved through metal coordination (Scheme 1). Scheme 1.…”
mentioning
confidence: 99%
“…[12][13][14][15] Furthermore,n one of these studies explore the concept demonstrated herein, which tackles the development of an ovel crystalline metal-donor-acceptor framework, in which control of the mutual orientation of the donor and fullerenebased acceptor was achieved through chemical bond formation, that is,m etal coordination. Despite the tremendous interest in self-assemblies (in particular,c oordination polymers such as covalent or metal-organic frameworks;COFs or MOFs) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and fullerene chemistry,t ot he best of our knowledge the prepared metal-organic fullerene-containing framework is the first example of ac rystalline hybridextended structure,inw hich control over mutual orientation of both donor and fullerene-based acceptor is achieved through metal coordination (Scheme 1). Scheme 1.…”
mentioning
confidence: 99%
“…Besides that, auxiliary ligands were also introduced to tune the flexibility of the frameworks [24]. It is interesting that there are relatively fewer reports on the flexible PCPs that are constructed with homometallic ions and pure H2bpdc ligand as T-shaped connecting modes, especially in type a [25].…”
Section: Introductionmentioning
confidence: 99%
“…To construct 3D flexible PCPs, although type a (T-shaped connecting mode) is reported more frequently, type c (linear bridging mode) is the most favorable option because the bpdc 2− ligands in the former type often act essentially as rigid spacers [20][21][22][23]. Besides that, auxiliary ligands were also introduced to tune the flexibility of the frameworks [24]. It is interesting that there are relatively fewer reports on the flexible PCPs that are constructed with homometallic ions and pure H 2 bpdc ligand as T-shaped connecting modes, especially in type a [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Furthermore,n one of these studies explore the concept demonstrated herein, which tackles the development of an ovel crystalline metal-donor-acceptor framework, in which control of the mutual orientation of the donor and fullerenebased acceptor was achieved through chemical bond formation, that is,m etal coordination. Despite the tremendous interest in self-assemblies (in particular,c oordination polymers such as covalent or metal-organic frameworks;COFs or MOFs) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and fullerene chemistry,t ot he best of our knowledge the prepared metal-organic fullerene-containing framework is the first example of ac rystalline hybridextended structure,inw hich control over mutual orientation of both donor and fullerene-based acceptor is achieved through metal coordination (Scheme 1). Scheme 1.…”
mentioning
confidence: 99%